Health Care While Homeless: Barriers, Facilitators, and the Lived Experiences of Homeless Individuals Accessing Health Care in a Canadian Regional Municipality. (November 2019) - Ramsay, Natalie; Hossain, Rahat; Moore, Mo; Milo, Michael; Brown, Allison
Persons struggling with housing remain significantly disadvantaged when considering access to health care. Effective advocacy for their needs will require understanding the factors which impact their health care, and which of those most concern patients themselves. A qualitative descriptive study through the lens of a transformative framework was used to identify barriers and facilitators to accessing health care as perceived by people experiencing homelessness in the regional municipality of Niagara, Canada. In-person, semi-structured interviews with 16 participants were completed, and inductive thematic analysis identified nine barriers and eight facilitators. Barriers included affordability, challenges finding primary care, inadequacy of the psychiatric model, inappropriate management, lack of trust in health care providers, poor therapeutic relationships, systemic issues, and transportation and accessibility. Facilitators included accessibility of services, community health care outreach, positive relationships, and shelters coordinating health care. Knowledge of the direct experiences of marginalized individuals can help create new health policies and enhance the provision of clinical care.